Analysis and Research on Multi-layer Docking Error of Complex Interlayer Column Module Based on Point Cloud. Issue 1 (March 2021) - Han, Jiang; Zhang, Qing; Zhang, Zifeng
Abstract: Modular design of large offshore oil and gas module reduces the construction difficulty of the whole building, but increases the cumulative error between modules. For large-scale steel structure buildings, the error between the inter-story column modules will affect the overall building stability. It is a feasible method to use point cloud to monitor the errors in real time, so as to trim the columns in time. The goal of this paper is to put forward a set of error analysis method which is suitable for point cloud pre-matching of interlayer integral column. This method includes the calculation and analysis of the center line angle error of each butt joint and the position error of butt joint center of gravity after transformation based on interlayer optimal matching. In practical work, the column structure with large error can be trimmed according to the calculated data.